Managing Customer Expectations and Priorities in Service Systems - Yu, Qiuping; Allon, Gad; Bassamboo, Achal; Iravani, Seyed (Management Science, 2018)
We study how to use delay announcements to manage customer expectations while allowing a firm to prioritize among customers with different sensitivities to time and value. We examine this problem by developing a framework that characterizes the strategic interaction between the firm and heterogeneous customers. When the firm has information about the state of the system, yet lacks information on customer types, delay announcements play a dual role: they inform customers about the state of the system, while they also have the potential to elicit information on customer types based on their response to the announcements. The tension between these two goals has implications for the type of information that can be shared credibly. To explore the value of the information on customer types, we also study a model where the firm can observe customer types. We show that having information on the customer type may improve or hurt the credibility of the firm. While the creation of credibility increases the firm’s profit, the loss of credibility does not necessarily hurt its profit. This paper was accepted by Noah Gans, stochastic models and simulation.